Compromised fidelity of B‐cell tolerance checkpoints in AChR and MuSK myasthenia gravis. Issue 6 (27th April 2016) - Lee, Jae‐Yun; Stathopoulos, Panos; Gupta, Sasha; Bannock, Jason M.; Barohn, Richard J.; Cotzomi, Elizabeth; Dimachkie, Mazen M.; Jacobson, Leslie; Lee, Casey S.; Morbach, Henner; Querol, Luis; Shan, Jing‐Li; et al.
Abstract: Objective: Myasthenia gravis (MG) is an autoimmune condition in which neurotransmission is impaired by binding of autoantibodies to acetylcholine receptors (AChR) or, in a minority of patients, to muscle specific kinase (MuSK). There are differences in the dominant IgG subclass, pathogenic mechanisms, and treatment responses between the two MG subtypes (AChR or MuSK). The antibodies are thought to be T‐cell dependent, but the mechanisms underlying their production are not well understood. One aspect not previously described is whether defects in central and peripheral tolerance checkpoints, which allow autoreactive B cells to accumulate in the naive repertoire, are found in both or either form of MG. Methods: An established set of assays that measure the frequency of both polyreactive and autoreactive B cell receptors (BCR) in naive populations was applied to specimens collected from patients with either AChR or MuSK MG and healthy controls. Radioimmuno‐ and cell‐based assays were used to measure BCR binding to AChR and MuSK. Results: The frequency of polyreactive and autoreactive BCRs ( n = 262) was higher in both AChR and MuSK MG patients than in healthy controls. None of the MG‐derived BCRs bound AChR or MuSK. Interpretation: The results indicate that both these MG subtypes harbor defects in central and peripheral B cell tolerance checkpoints. Defective B cell tolerance may represent a fundamental contributor to autoimmunity in MG and is of particular importance when considering the durability of myasthenia gravis treatment strategies, particularly biologics that eliminate B cells.